2003
DOI: 10.1046/j.1365-2265.2003.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body weight and weight loss on thyroid volume and function in obese women

Abstract: Our study suggests that thyroid volume and function may vary in obese women in association with body weight and fat mass; > 10% weight loss may affect thyroid volume and function, which however, is clinically insignificant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
123
5
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 31 publications
17
123
5
8
Order By: Relevance
“…Interestingly, the BMI of patients with subclinical hypothyroidism was significantly higher than euthyroid patients. The serum levels of TSH were higher in obese patients in some studies [37][38][39][40][41] but not in others [42,43]. The reason is still unclear because the BMI of patients with overt hypothyroidism was not different from the others also in our study.…”
Section: Discussionsupporting
confidence: 30%
“…Interestingly, the BMI of patients with subclinical hypothyroidism was significantly higher than euthyroid patients. The serum levels of TSH were higher in obese patients in some studies [37][38][39][40][41] but not in others [42,43]. The reason is still unclear because the BMI of patients with overt hypothyroidism was not different from the others also in our study.…”
Section: Discussionsupporting
confidence: 30%
“…This difference was related to the amount of lean body mass rather than to body weight by itself (59). After weight loss, a reduction in thyroid volume was also observed (60). Studies on children and adults also demonstrated that obesity is associated with a thyroid hypo-echogenic pattern at US, which occurs independently from thyroid autoimmunity (77,78).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 88%
“…Data regarding the circulating concentrations of thyroid hormones are less univocal because the serum levels of FT 3 were reported as increased, unchanged, or decreased. On the other hand, most studies reported a general trend toward low/normal levels of FT 4 in obese subjects (59,60,61,62,63,64,65,66). Lately, the relation between adiposity and serum TSH, FT 3 , and FT 4 was evaluated in a large, representative sample of the adult population from the National Health and Nutrition Examination Survey 2007-2008 (67).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 99%
“…A recent study from our group questioned whether an elevated serum TSH alone provides sufficient evidence for a diagnosis of subclinical hypothyroidism in patients with morbid obesity (19). Little has been reported on the morphology of the thyroid gland in adults with morbid obesity (20,21). A recent study, performed in obese children, showed for the first time that obesity is associated with structural changes in thyroid morphology, as assessed by US, which are unrelated to thyroid autoimmunity (22).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated hyperthyrotropinemia (a condition frequently encountered in patients with morbid obesity) (20) was defined as a raised serum level of TSH with normal FT 4 and FT 3 levels, in the absence of circulating thyroid Ab.…”
Section: Subjectsmentioning
confidence: 99%